Профілактика специфічних ускладнень після хірургічних втручань на щитоподібній залозі - Погорєлов, О. В.; Воскобойнік, О. Ю. (Clinical Endocrinology and Endocrine Surgery, 2009)
Various causes and consequences of specifiс сomplications in thyroid surgery — damage of laryngeal nerves and hypoparathyroidism — were reviewed.The main ways to prevent such complications were proposed. It was concluded that all endocrine surgeons should change traditionally used subcapsular methodic of thyroidectomy to extracapsular thyroidectomy with mandatory laryngeal nerves and parathyroids visualization and preservation. Author highly evaluated efficacy of additional modern prophylactic tools in thyroid surgery.